Literatur review pengembangan bahan ajar UKBM pada materi sistem peredaran darah manusia - Hikmah Fatimah; I Wayan Sumberartha; A. M. Setiawan (Jurnal Penelitian Pendidikan IPA, 2023)
Teaching materials commonly used in science learning include visual, audiovisual, and interactive multimedia teaching materials. The research design is a review of journals published in Sinta 2016-2021 with categories Sinta 6 to Sinta 2. The final result obtained is that there are 24 journals regarding the development of teaching materials. Teaching materials that have been developed include printed and digital teaching materials. Print teaching materials in the form of books, modules and comics. Digital teaching materials in the form of virtual reading rooms, videos and interactive CDs. Based on the SWOT analysis that has been carried out, there are weaknesses in the teaching materials that have been developed, namely they cannot be applied to independent learning without a teacher and are limited to material whose phenomena are easily observed by students. For this reason, UKBM (Independent Learning Activity Unit) teaching materials are very appropriate for students to study independently without a teacher. In addition, material for the circulatory system based on physics in this UKBM teaching material can help students understand abstract concepts that students cannot observe directly.